Anti-adhesive effect of chondrocyte-derived extracellular matrix surface-modified with poly-L-lysine - Song, Bo Ram; Park, In Su; Park, Do young; Kim, Young Jick; Kim, Moon Suk; Lee, Kyi Beom; Park, So Ra; Choi, Byung Hyune; Min, Byoung Hyun (Journal of Tissue Engineering and Regenerative Medicine, 2022)
After an injury, soft tissue structures in the body undergo a natural healing process through specific phases of healing. Adhesions occur as abnormal attachments between tissues and organs through the formation of blood vessels and/or fibrinous adhesions during the regenerative repair process. In this study, we developed an adhesion-preventing membrane with an improved physical protection function by modifying the surface of chondrocyte-derived extracellular matrices (CECM) with anti-adhesion function. We attempted to change the negative charge of the CECM surface to neutral using poly-L-lysine (PLL) and investigated whether it blocked fibroblast adhesion to it and showed an improved anti-adhesion effect in animal models of tissue adhesion. The surface of the membrane was modified with PLL coating (PLL 10), which neutralized the surface charge. We confirmed that the surface characteristics except for the potential difference were maintained after the modification and tested cell attachment in vitro. Adhesion inhibition was identified in a peritoneal adhesion animal model at 1 week and in a subcutaneous adhesion model for 4 weeks. Neutralized CECM (N-CECM) suppressed fibroblast and endothelial cell adhesion in vitro and inhibited abdominal adhesions in vivo. The CECM appeared to actively inhibit the infiltration of endothelial cells into the injured site, thereby suppressing adhesion formation, which differed from conventional adhesion barriers in the mode of action. Furthermore, the N-CECM remained intact without degradation for more than 4 weeks in vivo and exerted anti-adhesion effects for a long time. This study demonstrated that PLL10 surface modification rendered a neutral charge to the polymer on the extracellular matrix surface, thereby inhibiting cell and tissue adhesion. Furthermore, this study suggests a means to modify extracellular matrix surfaces to meet the specific requirements of the target tissue in preventing post-surgical adhesions.
Keywords: Animal model; Antiadhesion; Cells adhesion; Chondrocytes; Endothelial-cells; Extracellular matrices; In-vitro; In-vivo; Poly-L-Lysine; Tissue adhesion; Adhesives; Animals; Chondrocytes; Endothelial Cells; Extracellular Matrix; Polylysine; Tissue Adhesions; anti-adhesion; chondrocyte; extracellular matrix; poly-L-lysine (PLL); surface modification